2014
DOI: 10.1136/jnnp-2014-308736
|View full text |Cite
|
Sign up to set email alerts
|

Clinical relevance of serum antibodies to extracellularN-methyl-d-aspartate receptor epitopes

Abstract: ObjectiveThere are now a large number of requests for N-methyl-d-aspartate receptor autoantibody (NMDAR-Ab) tests, and it is important to assess the clinical relevance of all results, particularly when they are reported as ‘Low Positive’.MethodsThe clinical data of 56 patients found Positive or Low Positive by the Oxford live cell-based assay were reviewed. An autoimmune basis for the condition was assigned as ‘Definite’, ‘Possible’ or ‘Unlikely’. The number of core features (encephalopathy, psychiatric, cogni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
56
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 100 publications
(58 citation statements)
references
References 24 publications
2
56
0
Order By: Relevance
“…Indeed, low‐titer antibodies to VGKC complex or NMDARs have been found in some patients without autoimmune neurologic diseases,21, 25 and the fact that NMDARs were found in some children with generalized absence epilepsy makes them unlikely to be pathogenic in these cases. However, the binding to the surface of live hippocampal neurons, present in 8 of 17 sera, suggested that the antibodies could be pathogenic if they reach the brain parenchyma.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, low‐titer antibodies to VGKC complex or NMDARs have been found in some patients without autoimmune neurologic diseases,21, 25 and the fact that NMDARs were found in some children with generalized absence epilepsy makes them unlikely to be pathogenic in these cases. However, the binding to the surface of live hippocampal neurons, present in 8 of 17 sera, suggested that the antibodies could be pathogenic if they reach the brain parenchyma.…”
Section: Discussionmentioning
confidence: 99%
“…The specific NMDAR subunit targeted was not determined (GluN1 vs GluN2) and other control groups or additional confirmatory tests were not included. Indeed, using the same assay, these authors recently reported serum NMDAR antibodies in 23% of patients who had disorders considered unlikely to be immune mediated (e.g., posterior fossa glioma, atypical motor neuron disease, leukodystrophy, maple syrup urine disease, or idiopathic pure cerebellar syndrome) (Zandi et al, 2014). Given these findings, Zandi et al, have modified the interpretation of their assay scoring system, so that at least one of the three schizophrenia patients initially reported to harbor pathogenic auto-antibodies would currently be considered unlikely to have an immune associated disorder.…”
Section: Anti-nmdar Antibodies and Psychosismentioning
confidence: 97%
“…6 In a cohort of patients with diverse symptoms tested for NMDAR antibodies using a live cellbased assay similar to that used initially in this patient, 23% of cases considered antibody-positive did not have anti-NMDAR encephalitis or autoimmune disorders (e.g., glioma and leukodystrophy, among others). 7 In our patient, more specific and comprehensive immunologic testing including CSF and serum demonstrated that she did not have NMDAR antibodies. 2 This case emphasizes the difficulties in recognizing narcolepsy-cataplexy in children, the importance of prioritizing the clinical assessment over a serologic test especially when the symptoms do not fit with the test result, and the need for including CSF and comprehensive immunologic studies for NMDAR antibody determination.…”
mentioning
confidence: 99%